Evaluation of strength and electrical resistivity in cement mortars incorporating different biomass ashes - Karadag, Omer; Bundur, Zeynep Basaran; Cakir, Ozgur; Bilir, Turhan (SPRINGERNATURE, 2025)
The high carbon emissions of cement production necessitate mitigation strategies. One approach is partial cement replacement, for which biomass ash, a waste of biomass combustion for energy production, could be a viable candidate. This study investigates the effects of hazelnut shell ash and sugar beet pulp ash as partial cement replacements. Biomass ash properties and effects on setting time, strength, ultrasonic pulse velocity (UPV), and electrical resistivity were evaluated. Electrical resistivity was measured by two methods, including a newly introduced DC-based technique utilizing an insulation resistance tester. While hazelnut shell ash accelerated final setting by 73 min, sugar beet pulp ash delayed final setting by 186 min at the same 15% replacement rate. Both ashes reduced compressive and flexural strength, with the degree of reduction increasing with replacement rate; this effect was more pronounced for hazelnut shell ash. At a 5% replacement, hazelnut shell ash reduced compressive strength by 17.2 MPa at 28 days and 22.8 MPa at 90 days, while sugar beet pulp ash caused a smaller decrease of 4.7 MPa and 9.5 MPa, respectively. These results suggest that sugar beet pulp ash has a greater potential for performance improvement after mechanical activation application. Hazelnut shell ash improved electrical resistivity by 7% to 10% at a 5% replacement for both measurement methods, respectively. The DC-based method showed a strong correlation with the conventional Wenner test, with a Spearman's correlation coefficient of 0.964. UPV results remained largely unaffected by partial replacement. While biomass ash replacement poses challenges due to strength reduction, it offers advantages for rapid setting and improved resistivity. Future studies should investigate biomass fly ash and mechanical-chemical activation techniques to improve cementitious performance.
Keywords: Biomass ash; Electrical resistivity; Hazelnut shell ash; Sugar beet pulp ash; Supplementary cementitious materials; ACTIVATION; SUGARCANE; VELOCITY; Science & Technology - Other Topics; Environmental Sciences & Ecology